Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Exposure-informed ventilation control for nanoparticle pollutants in an enclosed industrial built environment: A laser metal deposition case study - Ying-Fang Wang; Thi-Cuc Le; Jing Wang; Yu-Tung Dai; Phuong-Uyen Tran; Van-Nghia Tran; Guo-Ping Chang-Chien; Lin-Chi Wang (Building and Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

Bio-inspired functionalization of PA1012 into piezoelectric ionomers via molecular asymmetry and ion-cluster polarization - Guangmou Cao; Rong Li; Qi Liang; Jingwen Liu; Pengyuan Luo; Haomeng Ma; Yang Yu; Linyi Cui; Le Xu; Jingjing Ma; Tong Lin; Liuchun Zheng (Chemical Engineering Journal, 2026)

Drying-wetting cycles alter the balance between physical fragmentation and leaching during leaf litter decomposition: a laboratory incubation experiment - Le-Lin Yu; Rui-Jing Chai; Qi-Han Tu; An He; Le-Cheng Ai; Rong Mao (Plant and Soil, 2026)

Mechanisms and control strategies of shrimp melanosis during storage: A review - Duanquan Lin; Qian Hong; Kai-Yuan Cao; Shu-Jun Hong; Yu-Lei Chen; Le-Chang Sun; Min-Jie Cao (Food Bioscience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Mitigating environmental impacts and reducing nitrogen footprint by novel tripartite pig husbandry with maximized waste recycling - Yu-Jen Lee; Bin-Le Lin; Yuki Ichisugi; Kazuya Inoue; Shohei Riya; Akihiko Terada (Journal of Cleaner Production, 2026)

Spatiotemporal relationships between mammal habitat suitability and recreational hiking intensity in Xiaowutaishan National Nature Reserve, China - Ming Yam Chan; Yue Cao; Zhicong Zhao; Pei Wang; Yunshuang Feng; Le Yu; Steve Carver; Xuehua Liu; Ruijia Zhu; Fengze Lin; Xialin Li; Yiqing Wang; et al. (Biological Conservation, 2026)

The GATA3-RFPL3-ASK1 axis suppresses breast cancer growth and lung metastasis - Kang Li; Chang Liu; Jun-Hui Yin; Yu-Ting He; Zhi-Zhi Xu; Wen-Jing Zhang; Jian-Qi Wang; Lu-Yao Hou; Jing Feng; Le-Min Lin; Xiu-Qing Duan; Yi Zhou; et al. (Apoptosis, 2026)

Dynamic remodeling of intramuscular structural proteins and its impact on abalone muscle quality during post-mortem cold storage - Hua Liu; Tian-Bo Zhang; Fu-Hao Zhang; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Jia-Yin Huang; Min-Jie Cao; Yu-Lei Chen (Food Chemistry, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Cadzow Filtering Method Based on Adaptive Singular Value Decomposition - Zhong-lin Cao; Dan Wang; Peng-yuan Sun; Le Li; Ding-yu Xiong; Wen Yang; Yin-yu Wen; Jing Bai (Applied Geophysics, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

The formation of autophagosomes in the development process of rice endosperm is affected by endogenous ascorbic acid - Le Yu; Mengwei Chen; Haoran Yan; Zeliang Ouyang; Xinyu Liu; Sitong Lin; Yixuan Tang; Zhipeng Xu; Chunyu Liu; Peiyi Chen; Liping Zhou; Yonghai Liu (Acta Physiologiae Plantarum, 2026)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Intercity red meat trade exacerbates the spatial inequality of greenhouse gas emissions and health burdens in China - Yue Zhao; Le Yu; Zhaohai Bai; Lin Ma (Journal of Environmental Management, 2025)

Uncovering AphBvp-mediated regulation of PirAvp/PirBvp toxins and biofilm formation in AHPND causing Vibrio parahaemolyticus - Michael Eniola Ayenero; Ramya Kumar; Han-Ching Wang; Phuoc Thien Le; Yu-Hsuan Chen; Chu Fang Lo; Shin-Jen Lin; Hao-Ching Wang (Fish & Shellfish Immunology, 2025)

Adaptive responses of soil phosphorus availability and plant phosphorus resorption to nitrogen enrichment-induced phosphorus limitation in a boreal peatland - Yu-Xin Ji; Le-Lin Yu; Zhen Zeng; Xian-Wei Wang; Rong Mao (Plant and Soil, 2025)

Controls over soil water-extractable organic matter quantity and biodegradability in alpine coniferous forests of Southwest China - Le-Lin Yu; Qi-Tong Wang; Hua-Jun Yin; Rong Mao (European Journal of Forest Research, 2025)

Mg-Fe isotopic constraint on the role of the lithosphere mantle in arc magmatism - Yang Yu; Xiao-Long Huang; Fan Yang; Yu Wang; Yi-Gang Xu; Iwan Setiawan; Sun-Lin Chung; Le Zhang; Guan-Hong Zhu (Lithos, 2025)

High-resolution assessment reveals underestimated human health risks of ammonia emissions in China's pig production - Yue Zhao; Le Yu; Zhenrong Du; Zhaohai Bai; Ling Liu; Tao Liu; Lin Ma (Journal of Cleaner Production, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Rapid detection of duck egg ovalbumin (D-OVA) in surimi via fluorescent immunochromatographic assay utilizing shark-derived single-domain antibody - Zhong-Lin Li; Ling-Jing Zhang; Kai-Yuan Cao; Jian-Lian Huang; Chang-Gong Zhang; Le-Chang Sun; Yu-Lei Chen; Min-Jie Cao (Food Chemistry, 2025)

A systematic approach to mitigate ozone pollution in northern Taiwan: Evidence from de-pollutant analysis - Thi-Thuy-Nghiem Nguyen; Manisha Mishra; Laddawan Noynoo; Thi-Cuc Le; Guan-Yu Lin; Tsai-Yin Lin; Racha Dejchanchaiwong; Perapong Tekasakul; Chuen-Jinn Tsai (Environmental Pollution, 2025)

Isochrysis zhanjiangensis exhibits protective effects against metabolic abnormalities induced by high-fat diet in mice - Mei Wu; Yu Bai; Yanrong Li; Kang Chen; Jingyang Le; Jian Li; Chengxu Zhou; Spiros N. Agathos; Lin Zhang; Xiaojun Yan; Jichang Han (Marine Life Science & Technology, 2025)

Fundamental study of horizontal wind velocity effect on PM2.5 and PM10 sampling accuracy of low-Cost sensors - Yi-Ming Lee; Thi-Cuc Le; Ying-Chang Chen; Gung-Hwa Hong; Guan-Yu Lin; Chuen-Jinn Tsai (Journal of Aerosol Science, 2025)

Zhengella sedimenti sp. nov. and Phycobacter sedimenti sp. nov., two novel bacteria isolated from coastal sediment with genomic and metabolic analysis - Pei-Ran Lin; Li-Jia-Yu Deng; Han-Zhe Zhang; Le Liu; Tian-He Liu; De-Chen Lu; Zong-Jun Du (Antonie van Leeuwenhoek, 2025)

Metabolomics unravels the formation pathway of advanced glycation end products in preserved egg yolk mediated by OH− during pickling - Le Chen; Zhuosi Yu; Shiqin Dong; Yiqun Huang; Xiaole Xiang; Yu He; Shugang Li; Lin Ye (Food Chemistry, 2025)

Updated insights into steady-modified anthocyanin food packaging: Novel strategies, characterization, application and future challenges - Jia-Yin Huang; Yu-Lei Chen; Duan-Quan Lin; Le-Chang Sun; Kang Liu; Ling-Jing Zhang; Ya-Qin Hu; Min-Jie Cao (Food Chemistry, 2025)

Astrocytic P2X7 receptor in retrosplenial cortex drives electroacupuncture analgesia - Wei Zhao; Si-Le Liu; Si-Si Lin; Ying Zhang; Chang Yu (Purinergic Signalling, 2025)

The effect of 254 nm ultraviolet C promoting ethanol-induced gastric injury healing - A potential physical factor therapy - Xiao Zhang; Dong-mei Li; Hong-long Chen; Xi-sheng Lin; Su-su Li; Le Yu; Nan Peng; Li-kang Wang; Na Wang; Yue-ming Gao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Synergistic effects of matrix metalloproteinases on the degradation of collagen in abalone (Haliotis discus hannai) - Yu-Lei Chen; Le-Le Su; Hua Liu; Tian-Bo Zhang; Guiling Li; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Min-Jie Cao (Food Chemistry, 2025)

Altered 3D genome reorganization mediates precocious myeloid differentiation of aged hematopoietic stem cells in inflammation - Xinyu Cui; Yu Dong; Qiang Zhan; Yixin Huang; Qianshu Zhu; Zihao Zhang; Guang Yang; Liping Wang; Shijun Shen; Jia Zhao; Zhiyi Lin; Jiatong Sun; et al. (Science China Life Sciences, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Multi-omics analysis reveals the potential mechanisms underlying long-term exercise-induced enhancement of learning and memory in male mice - Qiu-Xia Xiao; Hao-Yue Qin; Jun-Jie Chen; Chang-Le Fang; Qiu-Lin Wang; Qi-Jun Li; Shuai-Yu Zhu; Liu-Lin Xiong (Biogerontology, 2025)

Loss of KIFC1 activity induces spindle instability and actin defects during porcine oocyte maturation - Yu-Ran Wang; Peng-Jie Wang; Le-Yan Tao; Lin-Lin Hu; Qiang-Qiang Liu; Shao-Chen Sun; Jing-Xi Wei; Yue Wang (Theriogenology, 2025)

Blending of Sb2S3/PbS nanoparticles optimizes the CsPbI2Br perovskite/carbon electrode interface to facilitate efficient charge carrier transfer in perovskite solar cells - Fengli Liu; Haozhen Deng; Yu Jing; Lin Gao; Yuan Xu; Ruoshui Li; Chunyan Deng; Deng Wang; Zhenbo Du; Le Yang; Yicheng Cao; Jihuai Wu; et al. (Chemical Engineering Journal, 2025)

Curculigoside Regulates Apoptosis and Oxidative Stress Against Spinal Cord Injury by Modulating the Nrf-2/NQO-1 Signaling Pathway In Vitro and In Vivo - Yu Hou; Chaolun Liang; Lili Sui; Yang Li; Kai Wang; Xing Li; Kunrui Zheng; Haitao Su; Dianweng Xie; Dingkun Lin; Da Guo; Le Wang (Molecular Neurobiology, 2025)

Differential contribution of Cu2+ and OH− to the formation of Nε-carboxymethyllysine and Nε-carboxyethyllysine in preserved egg white during pickling - Le Chen; Zhuosi Yu; Shiqin Dong; Zixiao Li; Yongle Liu; Xiaole Xiang; Qun Huang; Shugang Li; Lin Ye (Food Chemistry, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Transparent mechanism of salted egg (white) hierarchically and synergistically driven by NaCl, NaOH and thermal treatment: Based on empirical data and molecular simulation - Le Chen; Shiqin Dong; Peng Xu; Zhuosi Yu; Yating He; Yongle Liu; Xiaole Xiang; Qun Huang; Shugang Li; Lin Ye (Food Chemistry, 2025)

Surface chemistry regulation enables highly durable superhydrophobic coatings with environmental robustness and pH-triggered recoatability - Mei-Lin Guo; Fang Wang; Ren-Yi Sun; Chun-Bo Li; Jin-Le Li; Fei Song; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

The improvement of gel properties and volatiles for frozen egg white melted assisted with ultrasound - Xiaole Xiang; Shiqin Dong; Le Chen; Yongle Liu; Yingqun Wu; Meijuan Yu; Gan Hu; Shugang Li; Lin Ye (Food Research International, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Jeotgalibacillus haloalkalitolerans sp. nov., a novel alkalitolerant and halotolerant bacterium, isolated from the confluence of the Fenhe River and the Yellow River - Ya-Fei Zhang; Yun-Lin Peng; Yong-Hui Xiao; Bing Yu; Ming-Yue Cao; Zhi-Ling Zhang; Le-Qun Huang; Yi Li (Antonie van Leeuwenhoek, 2024)

Stabilization of single crystal LiNi0.90Mn0.05Co0.05O2 via ZrO2 dual-functional coating enables superior performance for solid-state lithium battery - Chen Liu; Qiyue Luo; Lin Li; Chaochao Wei; Siwu Li; Xia Li; Wanming Li; Zihan Zhang; Zhongkai Wu; Zilin Jiang; Hui Yang; Long Zhang; et al. (Chemical Engineering Journal, 2024)

Integrated induction of silver resistance determinants and production of extracellular polymeric substances in Cupriavidus metallidurans BS1 in response to silver ions and silver nanoparticles - Jia-Xin Dai; Yanshuang Yu; Le-Xing You; Hong-Lin Zhong; Yuan-Ping Li; Ai-Jun Wang; Jon Chorover; Ren-Wei Feng; Hend A. Alwathnani; Martin Herzberg; Christopher Rensing (Chemosphere, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Expressional respones of hsp70 genes against abiotic and entomopathgenic stresses in four different noctuid larval species (Lepidoptera: Noctidae) - Yu-Ting Shi; Zheng Zhai; Zi-Yao Liu; Le Zhou; Hua Yang; Lin Chen; Yong-Sheng Zhang; Huan Yu (Pesticide Biochemistry and Physiology, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Atomically precise gold nanoclusters as ROS-scavenging clusterzymes to treat high-fat diet-induced obesity - Jialuo Ding; Mengyuan Zhao; Yeying Li; Kexin Zhang; Hanxing Chen; Xinying Hu; Le Li; Yu Su; Xun Yuan; Zhenkun Lin (Chemical Engineering Journal, 2024)

Effects of disposable face mask microplastics on soil properties and microbial communities - Liping Lin; Gongren Hu; Yangzi Lijin; Luowei Gan; Ruiqi Zhang; Ling Wang; Changhao Lu; Jianping Gao; Jiatai Lin; Le Yang; Yu Yan; Ruilian Yu (CATENA, 2024)

Hepatitis B virus core protein as a Rab-GAP suppressor driving liver disease progression - Yu Su; Fan Bu; Yuanfei Zhu; Le Yang; Qiong Wu; Yuan Zheng; Jianjin Zhao; Lin Yu; Nan Jiang; Yongxiang Wang; Jian Wu; Youhua Xie; et al. (Science Bulletin, 2024)

Awakening dumb Mn2+ mechanoluminescence site to achieve force, temperature and time-domain induced color tuning via trap-assisted energy transfer - Jiaqi Ou; Shuangqiang Fang; Haoliang Cheng; Dongjie Han; Qiangqiang Zhu; Yue Zhai; He Lin; Jiali Yu; Renjie Xu; RongJun Xie; Le Wang (Chemical Engineering Journal, 2024)

First record of the late Famennian conodonts in Qamdo, Tibet and their biostratigraphic implications - Yu-Ze Huang; Wen Guo; Wei Lin; Ping-Cuo Zhaxi; Le Yao; Ke-Yi Hu; Qiu-Lai Wang; Yu-Ping Qi (Palaeoworld, 2024)

Inorganic PM2.5 reduction in Kanto, Japan: The role of ammonia and its emission sources control strategies - Yu-Jen Lee; Bin-Le Lin; Kazuya Inoue (Environmental Pollution, 2024)

Photochemical oxidation of VOCs and their source impact assessment on ozone under de-weather conditions in Western Taiwan - Manisha Mishra; Pin-Hsin Chen; Guan-Yu Lin; Thi-Thuy-Nghiem Nguyen; Thi-Cuc Le; Racha Dejchanchaiwong; Perapong Tekasakul; Shih-Heng Shih; Ciao-Wei Jhang; Chuen-Jinn Tsai (Environmental Pollution, 2024)

Transplantation of MiR-28-5p-Modified BMSCs Promotes Functional Recovery After Spinal Cord Injury - Zhen Li; Haitao Su; Guandai Lin; Kai Wang; Yongming Huang; Yaqian Wen; Dan Luo; Yu Hou; Xuewei Cao; Jiaxian Weng; Dingkun Lin; Le Wang; et al. (Molecular Neurobiology, 2024)
Traumatic spinal cord injury (TSCI) is a prevalent central nervous system condition that imposes a significant burden on both families and society, affecting more than 2 million people worldwide. Recently, there has been increasing interest in bone marrow mesenchymal stem cell (BMSC) transplantation as a promising treatment for spinal cord injury (SCI) due to their accessibility and low immunogenicity. However, the mere transplantation of BMSCs has limited capacity to directly participate in the repair of host spinal cord nerve function. MiR-28-5p, identified as a key differentially expressed miRNA in spinal cord ischemia–reperfusion injury, exhibits differential expression and regulation in various neurological diseases. Nevertheless, its involvement in this process and its specific regulatory mechanisms in SCI remain unclear. Therefore, this study aimed to investigate the potential mechanisms through which miR-28-5p promotes the neuronal differentiation of BMSCs both in vivo and in vitro. Our results indicate that miR-28-5p may directly target Notch1, thereby facilitating the neuronal differentiation of BMSCs in vitro . Furthermore, the transplantation of lentivirus-mediated miR-28-5p-overexpressed BMSCs into SCI rats effectively improved footprint tests and Basso, Beattie, and Bresnahan (BBB) scores, ameliorated histological morphology (hematoxylin–eosin [HE] and Nissl staining), promoted axonal regeneration (MAP2 and growth-associated protein 43 [GAP43]), and facilitated axonal remyelination (myelin basic protein [MBP]). These findings may suggest that miR-28-5p-modified BMSCs could serve as a therapeutic target to enhance the behavioral and neurological recovery of SCI rats.

Comparison and development of scanning electron microscope techniques for delicate plant tissues - Jinhong Yuan; Lin Yang; Panpan Yu; Na Tang; Le Liu; Wenke Wang; Pei Wang; Qingxiang Yang; Siyi Guo; Junhua Li (Plant Science, 2024)

Characterization of spatial-temporal distribution and microenvironment source contribution of PM2.5 concentrations using a low-cost sensor network with artificial neural network/kriging techniques - Yi-Ming Lee; Guan-Yu Lin; Thi-Cuc Le; Gung-Hwa Hong; Shankar G. Aggarwal; Jhih-Yuan Yu; Chuen-Jinn Tsai (Environmental Research, 2024)

A top-down and in situ strategy for intrinsic acicular nanostructure enhanced ultradurable superhydrophobic and anti-icing aramid fabric - Jin-Le Li; Fang Wang; Chun-Bo Li; Ren-Yi Sun; Mei-Lin Guo; Gang Wu; Fei Song; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

Adaptive shifts in plant traits associated with nitrogen removal driven by phytoremediation strategies in subtropical river restoration - Yu Xin; Lin Liu; Xiao-Ru Yang; Le-Yang Yang; Shan-Bin Guang; Yu-Ming Zheng; Quan-Bao Zhao (Water Research, 2024)

Three new cardenolides from the fruits of Cascabela thevetia (L.) Lippold and their cytotoxic activities - Juan Long; Jia-Cheng Ouyang; Yu-Hao Luo; Qi-Jing Wu; Xiao-Tong Liao; Zhi-Le Chen; Qi-Lin Wang; Xiao-Yan Liang; Li Liu; Xue-Mei Yang; Xiao-San Li (Natural Product Research, 2024)

Expression of polyphenol oxidase of Litopenaeus vannamei and its characterization - Qian Hong; Yu-Lei Chen; Duanquan Lin; Ru-Qing Yang; Kai-Yuan Cao; Ling-Jing Zhang; Yi-Ming Liu; Le-Chang Sun; Min-Jie Cao (Food Chemistry, 2024)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Improved functionality and safety of peptides by the formation of peptide-polyphenol complexes - Duanquan Lin; Le-Chang Sun; Wei-Sen Huo; Ling-Jing Zhang; Yu-Lei Chen; Song Miao; Min-Jie Cao (Trends in Food Science & Technology, 2023)

Silver nanoparticle@catechol formaldehyde resin microspheres: One-pot synthesis and application for producing durable antimicrobial cotton fabrics - Lian-Yi Qu; Jiang-Long Liu; An-Le Yang; Lin Zhang; Ping Zhu; Ying-Jun Xu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Association between Asbestos Exposure and the Incidence of Kidney Cancer: a Weight-of-Evidence Evaluation and Meta-analysis - Fu-Shiuan Whitney Lee; Yu-Han Chen; Ngoc Dang Tran; Cheng-Kuan Lin; Le An Pham (Current Environmental Health Reports, 2023)

Direct immobilization of Se(IV) from acidic Se(IV)-rich wastewater via ferric selenite Co-precipitation - Zidan Yuan; Rui Su; Xu Ma; Le Yu; Yuanming Pan; Ning Chen; Roman Chernikov; Leo Ka Long Cheung; Reza Deevsalar; Ayetullah Tunc; Liang Wang; Xiangfeng Zeng; et al. (Journal of Hazardous Materials, 2023)

Study on the formation pathways of characteristic volatiles in preserved egg yolk caused by lipid species during pickling - Zhuosi Yu; Lin Ye; Yating He; Xinhong Lu; Le Chen; Shiqin Dong; Xiaole Xiang (Food Chemistry, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

Long-term field calibration of low-cost metal oxide VOC sensor: Meteorological and interference gas effects - Gung-Hwa Hong; Thi-Cuc Le; Guan-Yu Lin; Hung-Wen Cheng; Jhih-Yuan Yu; Racha Dejchanchaiwong; Perapong Tekasakul; Chuen-Jinn Tsai (Atmospheric Environment, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Properties of Pacific white shrimp (Litopenaeus vannamei) collagen and its degradation by endogenous proteinases during cold storage - Xu-Chen Xiao; Duanquan Lin; Kai-Yuan Cao; Le-Chang Sun; Yu-Lei Chen; Ling Weng; Ling-Jing Zhang; Min-Jie Cao (Food Chemistry, 2023)

Source-apportionment and spatial distribution analysis of VOCs and their role in ozone formation using machine learning in central-west Taiwan - Manisha Mishra; Pin-Hsin Chen; Wilfredo Bisquera; Guan-Yu Lin; Thi-Cuc Le; Racha Dejchanchaiwong; Perapong Tekasakul; Ciao-Wei Jhang; Ci-Jhen Wu; Chuen-Jinn Tsai (Environmental Research, 2023)

IRAK-M Ablation Promotes Status Epilepticus-Induced Neuroinflammation via Activating M1 Microglia and Impairing Excitatory Synaptic Function - Xiao-Shan Liang; Ting-Lin Qian; Yi-Fan Xiong; Xiao-Tao Liang; Yue-Wen Ding; Xiao-Yu Zhu; Yun-Lv Li; Jie-Li Zhou; Le-Yi Tan; Wei-Peng Li; Wei Xie (Molecular Neurobiology, 2023)

Enhanced removal of Cr(VI) by polyethyleneimine-modified bamboo hydrochar - Zi-Le Chen; Yu-Nan Zhang; Jian-Zhong Guo; Lin Chen; Bing Li (Environmental Science and Pollution Research, 2023)

Cartilage-targeting mRNA-lipid nanoparticles rescue perifocal apoptotic chondrocytes for integrative cartilage repair - Xinning Yu; Tengjing Xu; Huimin Shi; Jianqiao Hong; Xiaoqiang Jin; Le Cao; Jiajie Wang; Yunting Lin; Zongyou Pan; Siheng Wang; Jinghua Fang; Kaiwang Xu; et al. (Chemical Engineering Journal, 2023)

Gossypium mustelinum genome and an introgression population enrich interspecific genetics and breeding in cotton - Yang Yang; Chunyuan You; Nian Wang; Mi Wu; Yu Le; Maojun Wang; Xianlong Zhang; Yu Yu; Zhongxu Lin (Theoretical and Applied Genetics, 2023)

Three-dimensional quantitative structural-activity relationship and molecular dynamics study of multivariate substituted 4-oxyquinazoline HDAC6 inhibitors - Linan Zhao; Le Fu; Guangping Li; Yongxin Yu; Juan Wang; Haoran Liang; Mao Shu; Zhihua Lin; Yuanqiang Wang (Molecular Diversity, 2023)

Spatial-spectral-temporal connective tensor network decomposition for thick cloud removal - Wen-Jie Zheng; Xi-Le Zhao; Yu-Bang Zheng; Jie Lin; Lina Zhuang; Ting-Zhu Huang (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Environmental laws and ecological restoration projects enhancing ecosystem services in China: A meta-analysis - Tao Liu; Le Yu; Xin Chen; Hui Wu; Hui Lin; Chengxiu Li; Jiaru Hou (Journal of Environmental Management, 2023)

Confinement mechanism of FRP-confined concrete-encased cross-shaped steel columns - Le Huang; Tao Yu; Guan Lin; Shi-Shun Zhang (Engineering Structures, 2023)

Evaluation of small-sized mounds formation mechanisms in China's Zhurong landing region - Yu Lin (林雨); Jiannan Zhao (赵健楠); Le Wang (王乐); Jun Huang (黄俊); Liang Zhang (张良); Long Xiao (肖龙) (Icarus, 2023)

Fine-mapping and candidate gene analysis of qFL-c10-1 controlling fiber length in upland cotton (Gossypium hirsutum L.) - Ruiting Zhang; Chao Shen; De Zhu; Yu Le; Nian Wang; Yuanxue Li; Xianlong Zhang; Zhongxu Lin (Theoretical and Applied Genetics, 2022)

Mapping spatial-temporal nationwide soybean planting area in Argentina using Google Earth Engine - Yulin Shangguan; Xiyu Li; Yi Lin; Jinsong Deng; Le Yu (International Journal of Remote Sensing, 2022)

Identification, evolutionary analysis and functional diversification of RAV gene family in cotton (G. hirsutum L.) - Nosheen Kabir; Hai Lin; Xianhui Kong; Le Liu; Ghulam Qanmber; YuXuan Wang; Lian Zhang; Zhuojing Sun; Zuoren Yang; Yu Yu; Na Zhao (Planta, 2022)

A comparison of atmospheric geochemistry through lichens from volcanic and non-volcanic areas, north Taiwan - Le-Qi Lin; Hsueh-Yu Lu; Ju-Lien Pi; Tai-Sheng Liou; Wen-Fu Chen; Pei-Shan Hsieh (Journal of Earth System Science, 2021)

A Facile and Sensitive DNA Sensing of Harmful Algal Blooms Based on Graphene Oxide Nanosheets - Le Qiang; Yu Zhang; Chao Wu; Yingkuan Han; Suchun Wang; Yanyan Wang; Congcong Zhang; Guangzhou Liu; Qi Wu; Hong Liu; Ian R. Jenkinson; Jun Sun; et al. (Marine Biotechnology, 2020)

Oil palm plantation mapping from high-resolution remote sensing images using deep learning - Runmin Dong; Weijia Li; Haohuan Fu; Lin Gan; Le Yu; Juepeng Zheng; Maocai Xia (International Journal of Remote Sensing, 2020)

Anti- β -amyloid aggregation activity of enantiomeric furolactone-type lignans from Archidendron clypearia (Jack) I.C.N. - Yu-Xi Wang; Bin Lin; Le Zhou; Zhi-Yang Yan; Han Zhang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2020)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

Spatiotemporal crop NDVI responses to climatic factors in mainland China - Hongshuo Wang; Xiaoxuan Liu; Xiaodong Zhang; Pengxin Wang; Hui Lin; Le Yu (International Journal of Remote Sensing, 2019)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Plasma Amyloid-Beta Levels in Patients with Different Types of Cancer - Wang-Sheng Jin; Xian-Le Bu; Yu-Hui Liu; Lin-Lin Shen; Zhen-Qian Zhuang; Shu-Sheng Jiao; Chi Zhu; Qing-Hua Wang; Hua-Dong Zhou; Tao Zhang; Yan-Jiang Wang (Neurotoxicity Research, 2017)

PreSurgMapp: a MATLAB Toolbox for Presurgical Mapping of Eloquent Functional Areas Based on Task-Related and Resting-State Functional MRI - Huiyuan Huang; Zhongxiang Ding; Dewang Mao; Jianhua Yuan; Fangmei Zhu; Shuda Chen; Yan Xu; Lin Lou; Xiaoyan Feng; Le Qi; Wusi Qiu; Han Zhang; et al. (Neuroinformatics, 2016)

An Epigenetic Mechanism of High Gdnf Transcription in Glioma Cells Revealed by Specific Sequence Methylation - Bao-Le Zhang; Jie Liu; Yu Lei; Ye Xiong; Heng Li; Xiaoqian Lin; Rui-Qin Yao; Dian-Shuai Gao (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Sex Dimorphism Profile of Alzheimer’s Disease-Type Pathologies in an APP/PS1 Mouse Model - Shu-Sheng Jiao; Xian-Le Bu; Yu-Hui Liu; Chi Zhu; Qing-Hua Wang; Lin-Lin Shen; Cheng-Hui Liu; Ye-Ran Wang; Xiu-Qing Yao; Yan-Jiang Wang (Neurotoxicity Research, 2016)

Serum Amyloid-Beta Levels are Increased in Patients with Chronic Obstructive Pulmonary Disease - Xian-Le Bu; Guo-Qiang Cao; Lin-Lin Shen; Yang Xiang; Shu-Sheng Jiao; Yu-Hui Liu; Chi Zhu; Fan Zeng; Qing-Hua Wang; Ye-Ran Wang; Yong He; Hua-Dong Zhou; et al. (Neurotoxicity Research, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

A 60-s postconditioning protocol by percutaneous coronary intervention inhibits myocardial apoptosis in patients with acute myocardial infarction - Wen-Shu Zhao; Lin Xu; Le-Feng Wang; Li Zhang; Zhi-Yong Zhang; Yu Liu; Xiu-Lan Liu; Xin-Chun Yang; Liang Cui; Lin Zhang (Apoptosis, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)